TERMINATION OF PROSECUTION BASED ON RESTORATIVE JUSTICE IN ASSAULT CASES: A CASE STUDY AT THE PALEMBANG DISTRICT ATTORNEY’S OFFICE - Desi Arsean; Saipuddin Zahri; Mulyadi Tanzili (Jurnal Ilmiah Advokasi, 2025)
The prosecution authority, as part of the state’s law enforcement system, plays a strategic role in ensuring legal certainty, justice, and public order while upholding moral values and human dignity. In this context, the application of restorative justice has emerged as an alternative approach to resolving criminal cases, including assault offenses. This study examines the implementation of termination of prosecution based on restorative justice in an assault case handled by the Palembang District Attorney’s Office. The research adopts a normative juridical method, focusing on statutory regulations and prosecutorial guidelines governing restorative justice. The findings indicate that the termination of prosecution was influenced by several key factors: the suspect committed the offense for the first time, the offense carried a maximum statutory penalty of no more than five years’ imprisonment, and the value of losses or evidence did not exceed IDR 2,500,000. Additionally, the case demonstrated successful reconciliation between the perpetrator and the victim, supported by community approval. The study concludes that the application of restorative justice in this case reflects prosecutorial discretion aimed at achieving substantive justice, social harmony, and efficiency in criminal law enforcement.Keywords: termination of prosecution; restorative justice; assault cases; prosecutorial discretion